PHYTOCHEMICAL PROFILING ON HYPERICUM SPECIES - RaduÅ¡ienÄ—, J.; Janulis, V.; Ivanauskas, L.; Ã‡Ä±rak, C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Increased market demand for Hyperici herba has led to intensive studies on the chemistry and biological activities of different Hypericum species. The investigations were made on thirteen spontaneous Hypericum species from Turkey. HPLC method with photodiode array detection (PAD) was performed for chemical analyses of secondary metabolites. Eleven compounds with pharmacological interest, namely hyperforin, hypericin, pseudohypericin and phenolics such as chlorogenic acid, rutin, hyperoside, apigenin-7-O-glucoside, quercitrin, quercetin, kaempferol and amentoflavone, were separated and quantified in ethanolic extracts from stems, leaves and flowers. Among different plant parts, flowers were found to be principle organ for hypericin, pseudohypericin, hyperforine, chlorogenic acid, apigenin-7-O-glucoside, kaempferol, quercetin and amentoflavone accumulations, while hyperoside, rutin and quercitrin were accumulated mainly in leaves. Results from the present study indicated that H. adenotrichum, H. aviculariifolium, H. bupleuroides, H. hyssopifolium, H. montbretii, H. origanifolium, H. perfoliatum, and H. triquetrifolium accumulated higher concentrations of hypericin, pseudohypericin, quercitrin, hyperoside, amentoflavone, apigenin-7-O-glucoside or chlorogenic acid, when compared to H. perforatum, a well known commercial source of examined compounds. The occurrence of dark secretory glands in an organ is regarded as a reliable indicator of the presence of hypericins in Hypericum species [1]. The morphological observations of Hypericum species in the present study confirmed the corresponding phenomenon. We found a close relationship between dark gland density of leaves and hypericin content in several Hypericum species such as H. aviculariifolium, H. perforatum, H. montbretii, H. pruinatum and H. lydium. The research indicated Hypericum species of interest for further evaluation and new chemotaxonomical data of corresponding genus. [1] Robson, NBK: 1977. Studies in the genus Hypericum L. (Guttiferae). 2. Characters of the genus. Bull. Br. Mus. (Nat. Hist.) Bot. 8, 55-226.